2021
DOI: 10.1371/journal.pmed.1003660
|View full text |Cite
|
Sign up to set email alerts
|

Detection of significant antiviral drug effects on COVID-19 with reasonable sample sizes in randomized controlled trials: A modeling study

Abstract: Background Development of an effective antiviral drug for Coronavirus Disease 2019 (COVID-19) is a global health priority. Although several candidate drugs have been identified through in vitro and in vivo models, consistent and compelling evidence from clinical studies is limited. The lack of evidence from clinical trials may stem in part from the imperfect design of the trials. We investigated how clinical trials for antivirals need to be designed, especially focusing on the sample size in randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 54 publications
5
56
0
Order By: Relevance
“…This is because the treatment with RDV was initiated at day 0.5, which was close to the peak viral load in nose (i.e., day 0.680; Fig 1B ). Because only a very small fraction of target cells remain uninfected after the viral load peak ( 29 , 30 ), the number of ongoing de novo infections that the RDV can potentially interrupt is limited. Therefore, even if RDV blocked virus production with relatively high efficacy up to 100%, the viral load decay was not significantly influenced ( Figs 1E and S1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the treatment with RDV was initiated at day 0.5, which was close to the peak viral load in nose (i.e., day 0.680; Fig 1B ). Because only a very small fraction of target cells remain uninfected after the viral load peak ( 29 , 30 ), the number of ongoing de novo infections that the RDV can potentially interrupt is limited. Therefore, even if RDV blocked virus production with relatively high efficacy up to 100%, the viral load decay was not significantly influenced ( Figs 1E and S1A ).…”
Section: Resultsmentioning
confidence: 99%
“…There are various studies using mathematical models that can explain SARS-CoV-2 infection dynamics and give insight into treatment strategy ( 29 , 42 , 43 , 44 ). Another mathematical study of nasal viral load also showed a longer duration of virus shedding under RDV treatment; however, that study did not directly estimate treatment efficacy ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that if drugs such as remdesivir are administered very early, this may help control viral load, but may not have a major effect in severely ill patients. Iwanami et al also introduced a mathematical model to describe the within-host viral dynamics of SARS-CoV-2 and demonstrated that late timing of treatment initiation can mask the effect of antivirals in clinical studies of COVID-19 [7]. However, none of these models have included the impact of the immune response directly into their model, which plays an important role in the outcomes of the infection.…”
Section: Introductionmentioning
confidence: 99%
“…To describe the temporal change in viral load of each infected individual in the school or the office, a mathematical model describing the viral dynamics of SARS-CoV-2 was employed as in our previous studies Ejima, Kim, Ludema, et al, 2021;Iwanami et al, 2021;Jeong et al, 2021;Kim et al, 2021). Briefly explaining, the model is composed of two compartments: the viral load (copies/mL) at time ‫,ݐ‬ ܸሺ‫ݐ‬ሻ, and the ratio between the number of uninfected cells at time to and that at time 0, ݂ሺ‫ݐ‬ሻ.…”
Section: Sars-cov-2 Viral Dynamics Model and Viral Load Data Generationmentioning
confidence: 99%